The scoring skills which discriminate result, according set number in World Championship Volleyball 2010 - Joao, P. V.; Silva, M.; Lacerda, D.; Vaz, L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The study of the knowledge of the match isn't a recent concern, since one of the biggest challenges of the investigation has been, for a long time, the concern for the interpretation and understanding of the development of the specific knowledge in team sports. The aim of the present study intends to identify the actions of the game which discriminate the result (win/lose), according set number Methods: The sample of this study has been taken from the World Championship of Volleyball Male Seniors, Italy 2010. Were analyzed n=24 games, 3 were played in 5 sets, 12 in 4 sets and 9 in 3 sets which outcomes the result of 90 sets played throughout the 3rd round, which are the elite matches until the present study. These correspond to 24670 actions, in which 4083 services, 3434 receptions, 4906 attacks (3030 attacks after reception, 1876 attacks in transition), 2109 blocks, 1933 digs and 3299 sets. The Data Volley software was used in this research. To the data analysis was used the discriminating function (AD) in order to identify, throughout canonical structuring coefficient (CCE), the indicators which contribute the most to establish the maximum difference between the victories and defeats. We consider as relevant to the interpretation of the linear composite the |CCE| . 0,30 (Tabachnick & Fidell, 1996). The level of significance was established in 5%. The calculation of the results was made by the software SPSS version 17.0. Results: Regarding the total amount of the sample, the results suggest that the service point, the reception error and the block error were discriminating variables to the final outcome of the match. Only in the matches of 4 sets occurred significant differences in the actions of serve point, side out error, service error and attack error, contributing to the result of the match. Discussion: Regarding the results obtained throughout the positioning of the setter (defense zone and attack zone), the discriminating variables were service point, service error, excellent pass, pass error, excellent defense, side out error, counter attack point, attack point, excellent reception, side out point and reception error. We can say the action service point, it`s possible associate to the success (win). It`s very important training the efficacy of this action according the final outcome.